Rice-based cropping systems for enhancing productivity of food grains in India: decadal experience of AICRP - Deep, Mangal; Kumar, R. Mahender; Saha, Soumya; Singh, Aarti (Indian Farming, 2018)
Rice is a dominant crop; about 20% of global total human food calories are supplied by rice. More than 150 million ha were sown with rice in 2002, 90% of that in Asia. Demand for rice in Asia is projected to increase by 70% over the next 30 years. At 45 million ha, India has the largest national area of rice cropping . Much of this rice area is multi-cropped, and cropping patterns are very diverse. These varied cropping systems occur across a varied environment (e.g. weather, soils, topography), so quantitative assessment of a number of the ‘outputs’ of agriculture (e.g., crop yield, water use, soil erosion, nutrient leaching, greenhouse gas emissions) will benefit from detailed study of cropping systems and environmental variables.